Computer Anxiety and Personality Types of Accounting Students - FADILAH -; Syaiful Ali (The Indonesian Journal of Accounting Research, 2013)
This research examined the personality type and other factorssuch as gender and GPA that may contribute to computer anxiety amongaccounting students. The following questions guided this investigation:Does a relationship exist between computer anxiety and accountingstudent’s personality type? Does a relationship exist between accountingstudents’ gender, GPA and their computer anxiety?The data used in this paper were derived from a paper-based questionnairedistributed to accounting students at the Faculty of Economicsand Business of Universitas Gadjah Mada. One hundred and thirtynine(139) survey instruments were distributed. One hundred and thirtynine(139) instruments were returned, representing a response rate ofone hundred percent (100%). This study revealed that computer anxietydid exist among accounting students; there was a significant relationshipfor those students who were classified as sensing-intuitive and thinking-feeling and computerphobia; whereas accounting students’ genderand GPA did not influence their computer anxiety